P27 Conservative management of stage ia cervical cancer: outcomes following loop excision as a fertility sparing policy with critical emphasis on margin status. (1st November 2019) - Korompelis, P; Rundle, S; Adishesh, M; O'Donnell, R; Naik, R
Abstract : Introduction/Background: Controversies in stage IA cervical cancer include 1) need for radical treatment in IA2 disease, 2) lymphadenectomy in LVSI positive cases, 3) reflex hysterectomy as 1ry treatment or delayed hysterectomy after fertility completion. These controversies are highlighted by a trend towards conservative treatment consisting solely of loop excision. We present the largest series of a conservative treatment policy in stage IA cervical cancer. Methodology: A cross-referenced analysis utilising national and organisational databases was performed ensuring capture of all stage IA cervical cancers within a defined geographical area of the North of England over a 10 yr period (2006-16), population 1.6million women. The study objectives were to determine 1) regional incidence, 2) recurrence rate invasive disease, 3) recurrence rate CIN, and 4) reflex and delayed hysterectomy rates. Results: Diagnosis: 247 stage 1A cases were identified, 232(94%) 1A1 and 15(6%) IA2 (incidence 15/100, 000 women). 89% squamous histology, 5% LVSI positive, 4 occult cases at hysterectomy, remaining 243 loop diagnoses, 22% complete excision of invasive disease & CIN at first loop (11% incomplete excision invasive, 67% incomplete excision CIN). Treatment: 20% underwent one loop, 53% two loops and 1 patient 3 loops; 27% had hysterectomy. 7% underwent bilateral pelvic lymphadenectomy (0/17 positive nodes). Outcomes: Recurrence rate for invasive disease was 2/247(0.8%) with no deaths (median follow-up 46mths), CIN recurrence was 8/247(3%). Delayed hysterectomy rate was 13/177(7%). Both invasive recurrences were in stage IA1, LVSI negative cases. Case 1: hysterectomy with CIN3 at the vaginal margin. Case 2: loop treatment with CIN3 at the ectocervical margin. The difference in recurrence rates following hysterectomy (1.4%) or loop excision (0.6%) was non-significant (p=0.85). Conclusion: Recurrent invasive disease following a conservative treatment policy is <1%. Irrespective of loop excision/hysterectomy treatment, margin status defines the risk of recurrence, clear margins=0% (0/230), CIN incompletely excised=12% (2/17), CIN3 incompletely excised=33% (2/6)[p<0.05]. Disclosure: Nothing to disclose.